In vivo study of hypericin-loaded poloxamer-based mucoadhesive in situ gelling liquid crystalline precursor system in a mice model of vulvovaginal candidiasis - De Araújo, Patricia Rocha [UNESP]; Calixto, Giovana Maria Fioramonti [UNESP]; Araújo, Victor Hugo Sousa [UNESP]; Sato, Mariana Rillo [UNESP]; Rodero, Camila Fernanda [UNESP]; Oshiro-Junior, João Augusto; Bauab, Taís Maria [UNESP]; Chorilli, Marlus [UNESP] (Oxford University Press (OUP), 2021)
The present study reports the performance of the pigment hypericin (HYP)-loaded poloxamer-based mucoadhesive in situ gelling liquid crystalline precursor system (LCPS) for the treatment of vulvovaginal candidiasis (VVC) in mice. LCPS composed of 40% of ethoxylated and propoxylated cetyl alcohol, 30% of oleic acid and cholesterol (7:1), 30% of a dispersion of 16% poloxamer 407 and 0.05% of HYP (HYP-LCPS) was prepared and characterized by polarized light microscopy (PLM), small-angle X-ray scattering (SAXS) and ex vivo permeation and retention studies across vaginal porcine mucosa were performed. In addition, the antifungal properties of the HYP-LCPS were evaluated in a murine in vivo model; for this, infected C57BL female mice groups were treated with both HYP in solution and HYP-LCPS, and after 6 days colony forming unit (CFU)/ml count was performed. PLM and SAXS confirmed that HYP-LCPS is a microemulsion situated in boundary transition region confirming its action as an LCPS. When in contact with simulated vaginal fluid, HYP-LCPS became rigid and exhibited maltase crosses and bragg peaks characteristics of lamellar phase. Ex vivo permeation and retention studies showed that HYP-LCPS provides a localized treatment on the superficial layers of porcine vaginal mucosa. HYP-LCPS induced a significant reduction in the number of CFU/ml in the mice; thus this formulation indicated it is as effective as a commercial dosage form. It was concluded that LCPS maintains the biological activity of HYP and provides an adequate drug delivery system for this lipophilic molecule at the vaginal mucosa, being a promising option in cases of VVC.
Keywords: hypericin; liquid crystalline system; murine model; vulvovaginal candidiasis